Congenital Blindness and Autism Spectrum Disorder. Issue 2 (February 2021) - Conrad, Cassandra; Linnea, Kate; Augustyn, Marilyn
Abstract : CASE: Emily is a 10-year-old girl who is in fifth grade. She has known congenital blindness secondary to septo-optic dysplasia with bilateral optic nerve hypoplasia and precocious puberty. Emily was referred to a Developmental-Behavioral Pediatrics clinic for concerns of academic, social, and language challenges. Emily was born at term gestation after an uncomplicated pregnancy. At 4 months of age, she underwent ophthalmologic evaluation because of nystagmus, reduced visual tracking and response to light, and increased startle response to touch. An magnetic resonance imaging of the brain and orbits demonstrated bilateral hypoplastic optic nerves and the absence of posterior pituitary. Subsequent endocrinological evaluation for pituitary function was reassuring. Emily's early developmental milestones were delayed across all domains. She participated in early intervention programming including speech/language, physical, and occupational therapy with interval improvement in skills. She also received supports for low vision. In the elementary school, she received supports and services for low vision in a general education classroom. It was observed that Emily had reduced interest in her peers, a strong preference for routine, and distinctive play interests. As elementary school progressed, Emily had increasing challenges with academic achievement, despite performing well on formal testing in second grade. At a recent ophthalmology visit, Emily's best-corrected visual acuity was noted to be 20/800 in each eye. Neuropsychological testing was completed with visual accommodation and administration of measures with minimal visual requirements. Cognitive testing revealed variable verbal intellect and language skills. Academic testing revealed strong reading abilities and a relative weakness in math. Adaptive measures were notable for reduced function and highlighted social vulnerabilities. Parent measures regarding mood and behavior were not concerning. Emily's speech was noted to have a very distinctive prosody with notable response latency. Echolalia and scripting were appreciated, and Emily often asked about names and used made-up words. When excited, Emily flapped her arms and hands, jumped up and down, or clapped her hands quickly. Socially, Emily was engaged and seemed eager to please. She was able to participate in back-and-forth conversation. Although she often responded to social bids, she frequently directed the conversation to her own areas of interest. Emily looked in the direction of the examiner when talking to the examiner and when the examiner spoke. Although a diagnosis of autism spectrum disorder is under consideration, what special considerations are necessary in the context of congenital blindness?